Answer:
The product of the polynomials is 6p³ + 29p² + 22p - 21
Step-by-step explanation:
(2p + 7)(3p² + 4p - 3)
Use the foil method to multiply.
6p³ + 8p² - 6p + 21p² + 28p - 21
Combine like terms. Make sure you put the equation in standard form. This means that the exponential numbers will be ordered in descending form.
6p³ + 29p² + 22p - 21
P = 6s
s = 3.4
P = 6(3.4) = 20.4 cm
Answer:
f(e - 9) = 8e - 67
Step-by-step explanation:
To evaluate f(e - 9) substitute x = e - 9 into f(x)
f(e - 9) = 8(e - 9) + 5 = 8e - 72 + 5 = 8e - 67
Multiply 3 to the first bracket then multiply 2 to the second bracket. 3(a+2b) + 2(3a+b) = 3a+6b+6a+2b= 9a+8b
Answer:
3 3/5 miles
Step-by-step explanation:
6 3/4 divided by 1 7/8=
3 3/5